IMPLEMENTASI SANKSI PEMBERHENTIAN TIDAK DENGAN HORMAT ANGGOTA KEPOLISIAN YANG MELAKUKAN PENCURIAN DENGAN KEKERASAN (Studi Putusan Kode Etik Nomor: PUT. KKEP/148/X/2021 KKEP) - Bambang Hartono; Zainudin Hasan; An-Nisya Kholiza Pratami Putri (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2022)
Dishonorable discharge is the termination of the Police service period by an authorized official against a member of the Indonesian National Police for certain reasons. As for the formulation of the problem from this research, what are the factors that cause members of the police to commit criminal acts of theft with violence at the Lampung Regional Police, and what are the considerations for the commission of the Porli code of ethics in imposing sanctions on members of the Indonesian National Police who commit criminal acts of theft with violence. The approach used in this study is a normative juridical approach and an empirical juridical approach to obtain correct and objective research results. The results of this study indicate that the factors that cause police officers to commit crimes of theft and violence against civilians are based on 2 (two) driving factors, namely internal factors where the perpetrators have less self-control and weak faith and are far from the Almighty so that the perpetrators fell and committed the crime of theft with violence. In addition to these internal factors, external factors also greatly influence the occurrence of criminal acts of theft by violence committed by perpetrators, and the considerations of the Police Code of Ethics Commission in imposing sanctions on members of the National Police who commit criminal acts of theft by violence against civilians are 5 (five) points namely, firstly, the defendant IS has violated the Porli code of ethics, secondly, the testimony of witnesses who were in court, thirdly, the accreditor as the prosecutor has been able to prove his charges, fourthly, mitigating and providing facts.